Therapeutic approach of anaphylaxis. Issue 4 (August 2019) - Tanno, Luciana Kase; Alvarez-Perea, Alberto; Pouessel, Guillaume
Abstract : Purpose of review: Anaphylaxis is a recognized cause of death in all ages, which requires prompt recognition and treatment. We here propose to review the current and new pharmacological treatment of anaphylaxis in the view of the new knowledge in the field that can support the quality practice and empower allergists and health professionals with new tools that can be used to treat symptoms and prevent anaphylaxis. Recent findings: The recent description of phenotypes provides new insight and understanding into the mechanisms and causes of anaphylaxis through a better understanding of endotypes and application of precision medicine. Several biologic therapies and new devices are emerging as potential preventive treatment for anaphylaxis. Summary: Adrenaline (epinephrine) is still the first-line treatment for any type of anaphylaxis and is recognized as the only medication documented to prevent hospitalizations, hypoxic sequelae and fatalities. β2 -adrenergic agonists and glucagon remains as the second-line treatment of anaphylaxis, meanwhile glucocorticoids and antihistamines should be used only as third-line treatment. Their administration should never delay adrenaline injection in anaphylaxis. More intuitive adrenaline autoinjectors design and features are required as well as a worldwide availability of adrenaline autoinjectors. Biological drugs, such as omalizumab, have been used as therapeutic adjuvants as a preventive treatment of anaphylaxis, but cost-effectiveness should be considered individually. Understanding the specifications of underlying mechanisms can potentially support improvements in the patients' allergological work-up and open the opportunity of developments of potential new drugs, such as biological agents. Expanding knowledge with regard to the presentation, causes, and triggers for anaphylaxis among healthcare providers will improve its diagnosis and management, increase patient safety, and decrease morbidity and mortality.